Transitional cell carcinoma recurrence impacting intestinal diversion after radical cystectomy. Oncologic outcomes of a rare site of recurrence - Zattoni, Fabio (Cent European J Urol, 2020)
INTRODUCTION: Transitional cell carcinoma recurrence within an intestinal urinary diversion (TCCUD) after radical cystectomy (RC) is a rare condition with unknown origin, prognosis and treatment. The aim of this study was to describe treatment options and oncologic outcomes of this understudied site of recurrence in a multi-institutional case series. MATERIAL AND METHODS: TCCUD relapse cases after RC were investigated in a retrospective, multi-institutional study. Surgical approach and adjuvant chemotherapy were discussed. Early and late complications were described according to the Clavien-Dindo classification. Kaplan-Meier method was used to assess progression-free and cancer-specific survival. RESULTS: A total of 19 patients were selected. The most common presentation was gross hematuria. The median interval between RC and TCCUD was 51.2 months. Fifteen patients (78.9%) underwent surgical excision, and two underwent concomitant radical nephroureterectomy. In 12 (63.1%) cases the site of TCCUD was the uretero-ileal anastomosis. Tumor invading the muscularis of the intestinal diversion was described in 10 (52.6%) cases. Surgical complications occurred in 7/15 (46.6%) patients, of these two with Clavien-Dindo Grade III. Four patients (21.0%) underwent adjuvant chemotherapy and two (10.5%) both chemotherapy and radiation therapy. During follow-up 15 patients (78.9%) presented with other sites of recurrence, with lymph nodes (21.0%) and liver (15.7%) being the most common localizations. Recurrence free and overall survival rates were 36.8% and 15.8%, and 56.5% and 24.2%, respectively at 12 and 18 months. CONCLUSIONS: Most patients with TCCUD have invasive disease and a substantial percentage experience upper tract cancer during their disease course. TCCUD is often the herald of advanced disease and systemic progression, with poor progression-free and overall survival rates.